Previous Sternotomy as a Risk Factor in Minimally Invasive Mitral Valve Surgery - Minol, Jan-Philipp; Akhyari, Payam; Boeken, Udo; Albert, Alexander; Rellecke, Philipp; Dimitrova, Vanessa; Sixt, Stephan Urs; Kamiya, Hiroyuki; Lichtenberg, Artur (Frontiers in Surgery, 2018)
Background Cardiac redo surgery, especially after a full sternotomy, is considered a high-risk procedure. Minimally invasive mitral valve surgery (MIMVS) is a potential therapeutic approach. However, current developments in interventional cardiology necessitate additional discussion regarding the therapy of choice in high-risk patients. In this context, it is necessary to clarify the perioperative and postoperative risks induced by the factor previous sternotomy in the setting of MIMVS. Thus, we present a comparative study analyzing the outcome of MIMVS after previous sternotomy vs. primary operation. Methods We identified 19 patients who received isolated or combined mitral valve (MV) surgery via the MIMVS approach after previous full sternotomy (PS group) and compared the results to those of a group of 357 patients who received primary MIMVS (non-PS group). After a propensity score analysis, groups of n = 15 and n = 131, respectively, were subjected to a comparative evaluation. A 1-year follow-up analysis of functional cardiac parameters and clinical symptoms was performed, accompanied by a Kaplan–Meier analysis. Results Except for the rate of realized MV reconstructions (PS group: 53.8% vs. non-PS group: 85.5%; p = 0.011), no significant differences were to be noted within the intraoperative and early postoperative course. However, patients in the PS group experienced an increased intensive care unit stay length (PS group: 2 days, 95% CI, 1–8 vs. non-PS group: 1 day, 95% CI, 1–2; p = 0.072). The follow-up examinations revealed excellent functional and clinical outcomes for both groups. The Kaplan–Meier analysis displayed no significant difference regarding the postoperative mortality (p = 0.929) related to the patients at risk. Conclusion A previous sternotomy remains a risk factor for MIMVS and demands special attention in the early postoperative period. Nevertheless, the early- and late-term results concerning the functional and clinical outcomes suggest that the MIMVS procedure is satisfactory, even after a full sternotomy.